Tinjauan Faktor Penyebab Ketidaktepatan Waktu Pengembalian Sensus Harian Rawat Inap di RSUP dr. Soeradji Tirtonegoro Tahun 2020 - Dian Fadilah Ayu Lestari; Andri Permana Wicaksono; Atma Deharja (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Based on the results of preliminary studies conducted at the RSUP dr. Soeradji Tirtonegoro is known thehighest delay count is the Anggrek of 95% room and 4th Dahlia room of 80%. The delay has an impactwhich daily census returned is not timely, and be it can increase the work of officers for the next day andsending the recapitulation results to the reporting department is delayed. This study aims to observe theimplementation of the daily census and the factors causing the inaccuracy in returning the daily census ofhospitalization, the determination of the main causes of the problem are using a fishbone diagram. Thistype of research uses qualitative and are collected a data with observation, interview and documentation.The results of the main problem are Man (the work of the recapitulation officer is delayed and ineffective,the employee's indiscipline). Method (there is not written policies of Standard Operating Procedure, theofficer does not know the Standard Operating Procedure). Minutes (The deadline for retuning the dailycensus of hospitalization are not consistent). Machine (there are no features that support the daily censusof hospitalization in SINERGIS, daily inpatient census is manually). Money (there is no rewards).